Response of Bahiagrass hybrids to nitrogen fertilization or mixture with legumes - Eder Alexandre Minski da Motta; Larissa Arnhold Graminho; Miguel Dall’Agnol; Luciana Pötter; Carlos Nabinger; Cleber Henrique Lopes de Souza; Karine Cristina Krycki; Tamyris Nunes dos Santos; Roberto Luis Weiler; Mariana Rockenbach de Ávila (Revista Brasileira de Zootecnia, 2021)
ABSTRACT The objective of this work was to determine Paspalum notatum genotypes appropriate for the establishment of mixtures with temperate legumes and compare the productivity of mixtures with mineral-fertilized systems along two years. Four hybrids of P. notatum, ecotype Bagual and cv. Pensacola, were either subjected to mixtures with white clover (Trifolium repens) and birdsfoot trefoil (Lotus corniculatus) or fertilized with 0, 60, 120, 240, and 480 kg N ha−1 year−1. P. notatum leaf blades and stems and herbage accumulation denoted a management × year interaction. Herbage accumulation varied between the mixtures and fertilized systems in first year, while in the second year, herbage accumulation of mixed systems employing the B26, B43, C22, C9, and Bagual genotypes were similar to that of systems fertilized with 120 and 240 kg N ha−1. Hybrids B26 and C9 and ecotype Bagual, once made available to producers, could be indicated for mixtures with temperate legumes because they are superior to cv. Pensacola. Herbage accumulation in mixtures involving white clover plus birdsfoot trefoil and P. notatum genotypes is similar to that of mineral nitrogen-fertilized systems with 240 kg N ha−1, emphasizing the viability of mixed between these species.